Consumer credit finance charges : rate information and quotation - Mors, Wallace Peter (New York, National Bureau of Economic Research, Distributed by Columbia University Press, 1965)
This work traces the origins of the procedures used in determining the form in which finance charges are to be disclosed to show why the consumer is faced with varying forms of information. It goes on to analyze and evaluate the usefulness of this information to consumer borrowers.
Includes bibliographical footnotes.
oif 14/02/2019
Loans
Keywords: Finance charges; Consumer credit; Consumer credit - rate information